Prevalence of pulmonary nodules in dogs with malignant neoplasia as determined by CT. Issue 3 (19th February 2019) - Lamb, Christopher R.; Whitlock, James; Foster‐Yeow, Andrew T. L.
Abstract: In order to estimate the prevalence of pulmonary nodules in dogs with nonpulmonary malignant neoplasia, medical record descriptions of CT findings in dogs diagnosed with nonpulmonary malignant neoplasia were reviewed retrospectively. A total of 536 dogs were sampled from a single hospital. For malignant neoplasms with >10 affected individuals, prevalence of multiple pulmonary nodules at first CT was hemangiosarcoma 24 of 58 (41%), osteosarcoma 14 of 55 (26%), carcinoma 20 of 80 (25%), histiocytic sarcoma five of twenty‐one (24%), soft tissue sarcoma 13 of 57 (23%), adenocarcinoma 11 of 60 (18%), melanoma five of thirty‐seven (14%), lymphoma 10 of 76 (13%), mast cell tumor two of forty‐seven (4%), and squamous cell carcinoma zero of seventeen (0%). A solitary pulmonary nodule was identified at first CT in 33 (6%) dogs. Of these, nine had follow‐up CT, including two dogs in which the nodule disappeared, three dogs in which the size of the nodule did not change, and four dogs in which the nodule enlarged and additional pulmonary nodules appeared. Dogs with hemangiosarcoma were most likely to have signs of pulmonary metastasis at first CT, whereas dogs with mast cell tumor were infrequently affected, and no dog with squamous cell carcinoma had signs of pulmonary metastasis. A solitary pulmonary nodule at first CT was an indeterminate finding, potentially unassociated with neoplasia.